A comparative study of sevoflurane sedation with nitrous oxide sedation for dental surgery - Wang, C.Y.; Chiu, C.L.; Har, K.O.; Chan, C.; Rahman, Z.A.A. (2002)
This study compares the use of inhalation sedation using sevoflurane (group S) with inhalation sedation using nitrous oxide (group N) in patients undergoing bilateral extraction of third molar teeth under local anaesthesia. The study was designed as a cross-over study. Seventeen ASA I, day surgery patients were studied. Patients were randomly allocated to receive either 8 I/min 50 nitrous oxide in oxygen (group N) or same flow of 1 sevoflurane (group S) for the first procedure. Each patient then had the alternate method of sedation for the second procedure. There were no significant differences between the methods in patient co-operation and surgeon's satisfaction with sedation. Psychomotor tests were comparable in both groups. The patients were significantly more sedated in the group S compared to group N (P=0.004). Significantly more patients complained of an unpleasant odour group S (P<0.01) but none withdrew from the study for this reason. No adverse cardiorespiratory effects resulted from sevoflurane or nitrous oxide sedation. Both methods gave good amnesia during the procedure. There was high acceptance of both methods and the patients rated the technique as equally satisfactory. We conclude that inhalation sedation with sevoflurane is a suitable alternative method to nitrous oxide sedation.